Label-Free and Simple G-quadruplex-based Turn-Off Fluorescence Assay for the Detection of Kanamycin. (24th July 2018) - Zhu, Yuqing; Li, Wei; Tan, Shuzhen; Chen, Tianxiao
ABSTRACT: We have developed a label-free and turn-off fluorescence assay for the determination of kanamycin. The detection system consists of an aptamer for specifically recognizing kanamycin and two auxiliary probes functionalized with two GGG repeats at the 3′ or 5′ ends for signal reporting. Two probes both hybridize with the aptamer and then their G-rich sequences combine to form a G-quadruplex. When thioflavin T, a fluorophore, is bound to the G-quadruplex, the fluorescence intensity of the solution dramatically increases. Upon the addition of the kanamycin, the aptamer–kanamycin binding inhibits the hybridization of two probes and aptamer, and restrains the GGG repeats from getting closer to form the G-quadruplex structure, resulting a significant decrease in the fluorescence intensity. The proposed aptamer-based fluorescent sensing platform showed a linear relationship with the concentration of kanamycin from 0.6 to 20.0 nM. The detection limit was determined to be 0.33 nM. The sensing platform provides resistance to interferences from other antibiotics and can be used to efficiently recognize kanamycin in real samples.